The Transfer Of Power 1942-7 / V. iv - Brazier, Rodney (Oxford : Clarendon ; New York : Oxford University Press, 1973)
This new edition has been completely revised so as to incorporate and analyse all significant changes which have occurred since 1988 in the law and practice of British central government. The consequences of Margaret Thatcher's eviction from 10 Downing Street permeate several chapters: in particular, changes in the Conservative Party's leadership election rules, and the consequences of John Major's different style of government are noted. Mr. Major has also authorized the official publication for the first time of information about Cabinet committees and of the code of conduct for Ministers, and these are fully described and analysed.
A steady stream of memoirs and diaries has flowed from the pens of former Ministers, all of which have been evaluated and are referred to wherever they throw light on government practice. The text also contains a full discussion of the consequences of the Official Secrets Act 1989. A new chapter on the Opposition has been added to reflect the importance of the potential government and its part in the daily work of Parliament. Detailed changes in the practice of both Houses of Parliament are incorporated and major reforms of the qualifications for judges are described.
1. Introductory -- 2. Choosing a Prime Minister -- 3. Government Formation From a Hung Parliament -- 4. The Transfer of Power -- 5. The Prime Minister -- 6. The Cabinet -- 7. Ministers and Departments -- 8. The Opposition -- 9. Constitutional Monarchy -- 10. The House of Commons -- 11. The House of Lords -- 12. The Constitutional Position of the Judges -- App. A. Senior Ministers since 1945 -- App. B. The party Leadership election rules -- App. C. The formal resignation and appointment of Ministers: A memorandum by the Clerk of the Privy Council -- App. D. Changes in ministerial titles and government departments since 1900.
Includes bibliographical references and index.
Keywords: Great Britain -- Politics and government -- 1979-1997.